2020
DOI: 10.1038/s41598-020-77894-2
|View full text |Cite
|
Sign up to set email alerts
|

A cyanobacterial photorespiratory bypass model to enhance photosynthesis by rerouting photorespiratory pathway in C3 plants

Abstract: Plants employ photosynthesis to produce sugars for supporting their growth. During photosynthesis, an enzyme Ribulose 1,5 bisphosphate carboxylase/oxygenase (Rubisco) combines its substrate Ribulose 1,5 bisphosphate (RuBP) with CO2 to produce phosphoglycerate (PGA). Alongside, Rubisco also takes up O2 and produce 2-phosphoglycolate (2-PG), a toxic compound broken down into PGA through photorespiration. Photorespiration is not only a resource-demanding process but also results in CO2 loss which affects photosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…In recent years, different strategies to improve crop yields have been proposed and reviewed, such as: (i) introducing photorespiratory bypasses (Betti et al, 2016; Hagemann and Bauwe, 2016; South et al, 2018; Eisenhut et al, 2019; López‐Calcagno et al, 2019; Maurino, 2019; Shen et al, 2019; Khurshid et al, 2020; Wang et al, 2020; Abbasi et al, 2021); (ii) introducing algal/cyanobacterial carbon concentrating mechanisms (McGrath and Long, 2014; Rae et al, 2017; Long et al, 2018; Atkinson et al, 2020; Hennacy and Jonikas, 2020; Chen et al, 2021; Rottet et al, 2021); (iii) introducing the C4 photosynthesis pathway into C3 plants (Ermakova et al, 2020, 2021a); (iv) improving mesophyll conductance (Hanba et al, 2004; Xu et al, 2019; Lundgren and Fleming, 2020; Ermakova et al, 2021c); (v) modifying metabolic processes (Rossi et al, 2015; South et al, 2019); and (vi) modifying circadian rhythms and introducing chronocultures (Steed et al, 2021). During the second half of the 20th century, the Green Revolution led to improved grain yields through conventional breeding techniques and improved pest/disease control.…”
Section: Introduction—why Do We Need Crops With Increased Yields?mentioning
confidence: 99%
“…In recent years, different strategies to improve crop yields have been proposed and reviewed, such as: (i) introducing photorespiratory bypasses (Betti et al, 2016; Hagemann and Bauwe, 2016; South et al, 2018; Eisenhut et al, 2019; López‐Calcagno et al, 2019; Maurino, 2019; Shen et al, 2019; Khurshid et al, 2020; Wang et al, 2020; Abbasi et al, 2021); (ii) introducing algal/cyanobacterial carbon concentrating mechanisms (McGrath and Long, 2014; Rae et al, 2017; Long et al, 2018; Atkinson et al, 2020; Hennacy and Jonikas, 2020; Chen et al, 2021; Rottet et al, 2021); (iii) introducing the C4 photosynthesis pathway into C3 plants (Ermakova et al, 2020, 2021a); (iv) improving mesophyll conductance (Hanba et al, 2004; Xu et al, 2019; Lundgren and Fleming, 2020; Ermakova et al, 2021c); (v) modifying metabolic processes (Rossi et al, 2015; South et al, 2019); and (vi) modifying circadian rhythms and introducing chronocultures (Steed et al, 2021). During the second half of the 20th century, the Green Revolution led to improved grain yields through conventional breeding techniques and improved pest/disease control.…”
Section: Introduction—why Do We Need Crops With Increased Yields?mentioning
confidence: 99%
“…In addition to this, there is a need to examine the nutrient requirements of transgenic plants expressing partial or complete bypasses under ambient atmospheric CO 2 (C a ) levels as modifications in N availability or allocation could lead to an enhancement of A . In a kinetic bypass model study, we evaluated the effect of the complete glycolate decarboxylation pathway on A and reported increase in A at ambient C i concentrations, but in the A -Ci curve, the bypass model attained steady state even at 380 ppm and further increases in C i up to 950 ppm had no effect on A ( Khurshid et al, 2020 ). Furthermore, we identified that the higher C i requires more inorganic phosphate (Pi) to cause any further increase in A , which was shown in both the C 3 and bypass models ( Khurshid et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a kinetic bypass model study, we evaluated the effect of the complete glycolate decarboxylation pathway on A and reported increase in A at ambient C i concentrations, but in the A -Ci curve, the bypass model attained steady state even at 380 ppm and further increases in C i up to 950 ppm had no effect on A ( Khurshid et al, 2020 ). Furthermore, we identified that the higher C i requires more inorganic phosphate (Pi) to cause any further increase in A , which was shown in both the C 3 and bypass models ( Khurshid et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the implemented bypasses described above, there are some promising alternative bypasses that could be experimentally tested in plants. Such as similar to the third bypass in the chloroplast, glycolate is converted to two molecules of CO 2 completely ( Eisenhut et al, 2008 ; Claassens et al, 2020 ; Khurshid et al, 2020 ). In these bypasses, glycolate is first converted to formate with one molecule of CO 2 release by three or four enzymes and then formate oxidizes to CO 2 by formate dehydrogenase (FDH) ( Eisenhut et al, 2008 ; Claassens et al, 2020 ; Khurshid et al, 2020 ) ( Figure 2 , fonts marked by orange color).…”
Section: Potentially Achieved Photorespiratory Bypasses In Plantsmentioning
confidence: 99%
“… The potentially achieved biosynthetic bypasses of photorespiration in plants. Two glycolate decarboxylation bypasses are marked by orange ( Eisenhut et al, 2008 ; Claassens et al, 2020 ; Khurshid et al, 2020 ). GDH, glycolate dehydrogenase; HDH, hydroxyacid dehydrogenase; ODC, oxalate decarboxylase; FDH, formate dehydrogenase; AGODH, CoA-acylating glyoxylate dehydrogenase; OXC, oxalyl-CoA decarboxylase; FRC, formyl-CoA transferase.…”
Section: Potentially Achieved Photorespiratory Bypasses In Plantsmentioning
confidence: 99%